THEORETICAL PRINCIPLES OF EDUCATION OF NATIONAL ETHICS SKILLS IN EDUCATIONAL INSTITUTION STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article describes the importance of the formation of national etiquette skills in special educational institutions, its regulatory and legal bases, specific features of its components, conditions, and pedagogical requirements for it.